Quality of Sleep among Diabetes and Non–Diabetes–Pilot Study (Indian Journal of Public Health Research & Development, 2020)
Almost everyone has trouble sleeping once in a while, but if occasional episodes of sleep escalate into anunhealthy night time routine, and it will hamper the productivity and sap the patients quality of life1.Objective: Of this pilot study was to compare the quality of sleep among patients with and without diabetes.Methodology: Quantitative approach with a descriptive design was used. A non-probability conveniencesampling technique was used to select samples in this study. A semi-structured questionnaire prepared by theinvestigator was used to collect the socio-demographic and clinical data from the subjects. A standardizedPittsburgh Sleep Quality Index tool was used to compare the sleep quality among 37 diabetic and 37 nondiabeticsubjects.Results: The study findings shows that in both diabetic (DM) and non-diabetic (NDM) subjects majority ofthe subjects 75.7% and 43.2% respectively were of the age group of 56-65 years. In both the groups majoritywere male (DM-24 and NDM – 27). The results also showed that among the groups most of the subjectswere had high school education, were employed,and were married and had a monthly income >Rs.15,000.Among diabetic subjects 22(59.4%) were hypertensive whereas among non-diabetic subjects 9(51.35%)were hypertensive. The study findings revealed that, majority of the subjects with diabetes had poor sleepquality 78.4% (29), whereas among non-diabetic subjects only 51.4% (19) subjects reported poor sleepquality and the quality of sleep among non-diabetic subjects were better than diabetic subjects at (p=0.014).Conclusion: As a healthcare practitioner, the health care providers should focus their attention to the qualityof sleep of their patients and should take initiative to make the people to aware about the importance of sleepin their day to day life to live healthy.
Keywords: Diabetes Mellitus, Quality of Sleep, Non-diabetes